2018
DOI: 10.1186/s13662-018-1805-6
|View full text |Cite
|
Sign up to set email alerts
|

Hopf bifurcation analysis of a delayed SEIR epidemic model with infectious force in latent and infected period

Abstract: In this paper, we analyze a delayed SEIR epidemic model in which the latent and infected states are infective. The model has a globally asymptotically stable disease-free equilibrium whenever a certain epidemiological threshold, known as the basic reproduction number R 0 , is less than or equal to unity. We investigate the effect of the time delay on the stability of endemic equilibrium when R 0 > 1. We give criteria that ensure that endemic equilibrium is asymptotically stable for all time delays and a Hopf b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Hence from the set of parameter values given in Eq. (31) we obtain that the endemic equilibrium point E * is locally asymptotically stable, which is confirmed by the Routh-Hurwitz criterion.…”
Section: Numerical Simulationssupporting
confidence: 70%
See 4 more Smart Citations
“…Hence from the set of parameter values given in Eq. (31) we obtain that the endemic equilibrium point E * is locally asymptotically stable, which is confirmed by the Routh-Hurwitz criterion.…”
Section: Numerical Simulationssupporting
confidence: 70%
“…In addition to computer virus models with time delay, there are also some other dynamical models with time delay, which have shown that time delay causes problems such as instability and restrict the conceivable performance of the control systems. For example, the predator-prey model [27][28][29][30], the epidemic model [31][32][33][34][35], and the neural network model [36][37][38][39]. All the mentioned works about delayed dynamical models have shown that time delay can produce complicated nonlinear phenomena with the change of time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations